A Bioelectrochemical System for Waste Degradation and Energy Recovery From Industrial Coffee Wastewater - Agudelo-Escobar, Lina María; Cabrera, Santiago Erazo; Avignone Rossa, Claudio (Frontiers in Chemical Engineering, 2022)
The primary production of coffee involves the extensive use of water resources, since it is not only used in the cultivation of coffee plantations, but it is also required in the processing of the coffee berry to obtain high quality green beans. It is calculated that for every kg of dry coffee grain produced, up to 40 L of water are consumed. The generation and disposal of liquid waste derived from the coffee harvest is a significant environmental problem, since most coffee growers are small producers which have no access to efficient technologies for wastewater treatment. This situation leads to the disposal of these liquid wastes in natural water sources, generating environmental pollution and public health problems. Bioelectrochemical Systems (BES) have been proposed as an alternative to conventional wastewater treatments, designed as a bioremediation strategy or for secondary wastewater treatment systems. Among BES, microbial fuel cells (MFCs) are designed to exploit the metabolic capability of microorganisms to degrade the organic matter present in the waste. Anodophilic microorganisms use electrodes as terminal electron acceptors, generating a flow of electrons that can be used in the generation of electricity. In this work, we evaluated the ability of native microbial communities to degrade the organic matter present in wastewater from the coffee agroindustry and its electrogenic potential for the co-generation of electricity using an alternative microbial fuel cell design. Wastewater samples obtained at different stages of the coffee wet processing process were used as inoculum and feedstocks. The system was operated in fed-batch, in both open and closed-circuit conditions, for 60 days. The degree of decontamination or bioremediation of the wastewater was established by determining physicochemical parameters. For the characterization of the native microbial community, microscopic and molecular techniques were used and the electrogenic potential was established by assessing the electrochemical performance of the system. With the proposed bioelectrochemical system, a reduction of up to 70% of the initial content of organic matter of the residual water from the coffee benefit was achieved, and open circuit voltages of up to 400 mV were recorded, comparable to those reported for conventional BES.